Nutrient intake amongst rural adolescent girls of Wardha - Maliye C; Deshmukh P; Gupta S; Kaur S; Mehendale A; Garg B (Wolters Kluwer Medknow Publications, 2010)
Objective: To assess the nutrient intake of rural adolescent girls. Materials and Methods: The cross-sectional study was carried in four adopted villages of the Department of Community Medicine, M.G.I.M.S., Sewagram. A household survey was carried out in the villages. A list of all the adolescent girls in the age group of 10-19 years was prepared by enumeration through house-to-house visit. All adolescent girls were included in the study. A pre-designed and pre-tested questionnaire was used to collect data on socio-demographic variables and anthropometric variables. A 24 h recall method was used to assess nutrient intake. Data generated was entered and analyzed using epi_info 2000. Nutrient intake was compared with ICMR Recommended Dietary Allowances. Nutritional status was assessed by BMI for age. Results: The mean height of the adolescent girls was 142.9 cm. Overall, 57% of the adolescents were thin (BMI for age <5 th percentile for CDC 2000 reference) and 43% of the adolescents were normal (BMI for age between 5 th - 85 th percentile for CDC 2000 reference). The average energy intake, which was 1239.6±176.4 kcal/day, was deficient of RDA by 39%. The average protein intake was 39.5±7 gm/day. It was deficient by 36% and the average iron intake, which was 13.2±2.5 mg/day, was deficient by 48%. Conclusion: The findings reiterate the dietary deficiency among adolescent girls which adversely affects the nutritional status. If the poor nutritional status is not corrected promptly before they become pregnant, it adversely affects the reproductive outcome. If we have to meet out the goals of Reproductive and Child Health Program, intervention strategies to improve the dietary intake of adolescent girls are needed so that their requirements of energy, protein, vitamins and minerals are met.